Cyber-physical system based frameworks for real-time Airborne hazard detection and monitoring Using intelligent gas sensor systems - Kumar, Kanak (IIT(BHU) Varanasi, 2023)
Abstract is available in the content.
Keywords: Cyber-physical system based; frameworks for real-time; Airborne hazard detection; and monitoring Using; intelligent gas sensor systems